UNRAVELING RELATIVELY UNCLEAR STORIES: A NARRATIVE ANALYSIS OF STUDENT-TEACHERS’ IDENTITY WORK - Mambu, Joseph Ernest (Universitas Pendidikan Indonesia, 2017)
Motivated by the need for more empirical evidence of Indonesian-based novice teachers’ identity, this paper aims to uncover nonnative English-speaking student-teachers’ identity work in their relatively unclear narratives of teaching practicum experiences. (Narrative) discourse analytical perspectives were used to examine two student-teachers’ narratives that were elicited in individual interviews. An analysis of one female student-teacher’s narrative suggests that digressive plotting—at first glance—and the use of some cryptic, and sometimes idiosyncratic, expressions can be re-constructed by a discourse analyst such that the overall structure and message of the speaker’s narrative is streamlined. A relatively unclear narrative was also produced by a male student-teacher. Different from the female student-teacher’s detailed narrative with digressive plotting, the male student-teacher’s plotting was underdeveloped. However, both student-teachers exercised their agency, though in different degrees, when framing their personal stories. This paper concludes with the notion that the narrative analysis makes more visible student-teachers’ identity work in which they, with their sense of agency, overcame (inter)personal tensions or struggles narrated in stories which are not necessarily clear.